A Baseline Study of Oxygen Saturation in Parafoveal Vessels Using Visible Light Optical Coherence Tomography - Wang, Jingyu; Song, Weiye; Sadlak, Natalie; Fiorello, Marissa G.; Desai, Manishi; Yi, Ji (Frontiers in Medicine, 2022)
The retinal macula is at the center of our visual field, and thus pathological damage in the macula significantly impacts an individual’s quality of life. The parafoveal vessels form the inner retina provide oxygen perfusion, and the measurement of parafoveal oxygen saturation (sO2) can evaluate macular metabolism and provide pathophysiological insight. In this paper, for the first time, we present a baseline study of microvascular oxygen saturation (sO2) in perifoveal region using visible light optical coherence tomography (VIS-OCT) on normal eyes. The arterial and venous sO2 from all eyes was 92.1 ± 7.1 (vol %) and 48.4 ± 5.0 (vol %) (mean ± SD), respectively. Arteriovenous sO2 difference was 43.8 ± 9.5 (vol %). Marginal correlation was found between venous sO2 and intraocular pressure (IOP) among eyes. No significant correlation was found between sO2 and vessel topological features, including length, diameter, and distance to fovea. This baseline study could serve as a benchmark for the future sO2 investigation of retinal macular pathologies.